Try Out Ujian Certified Accurate Professional (CAP) Pada Musyawarah Guru Mata Pelajaran (MGMP) Akuntansi Se-Kabupaten Kudus - Febra Robiyanto; Naila Rizki Salisa; Zuliyati Zuliyati (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2024)
Muria Kudus University's Community Service Program (PKM) this time is partnering with the Accounting Subject Teachers' Conference (MGMP) throughout Kudus Regency which will be held at SMK 1 Kudus. This activity aims to increase knowledge related to accounting applications by providing an introduction to online accounting software (Accurate) for the Accounting Subject Teachers' Conference (MGMP) throughout Kudus Regency. The form of this activity is training and assistance in using accounting applications via technology assisted by Accurate online from March 29 - April 3 2024 in collaboration with PT Ultima Tekno Solusindo. Followed by a tryout for the Certified Accurate Professional (CAP) exam on April 12 2024, at the Accounting Subject Teachers' Conference in Kudus Regency, until they receive the Certified Accurate Professional (CAP) title. So it is hoped that this knowledge will be useful for accounting students and the wider community. The output of this activity is increased improvement in Human Resources (HR), increased knowledge for the Accounting Subject Teachers' Conference throughout Kudus Regency, as well as outputs in community service journals.